Compositional Analysis of Cement Raw Meal by Near-Infrared (NIR) Spectroscopy. (12th December 2019) - Xiao, Hang; Yang, Zhenfa; Zhang, Lei; Feng, Dejun; Zhang, Faye; Jiang, Mingshun; Sui, Qingmei; Jia, Lei
Abstract: A rapid and accurate method is presented to determine CaCO3, SiO2, Fe2 O3, and Al2 O3 in cement raw meal using near-infrared (NIR) spectroscopy. Multiplicative scatter correction (MSC) was employed to eliminate the scattering signal and partial least squares (PLS) regression was used to build the analysis model. The results demonstrated good performance by this approach for the determination of CaCO3, SiO2, Fe2 O3, and Al2 O3 . NIR spectroscopy exhibits the feasibility to characterize the quality of cement raw meal. Compared with prompt gamma neutron activation analysis (PGNAA) and X-ray fluorescence (XRF), this method is more efficient and safer.